2012
DOI: 10.3892/br.2012.40
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic abnormalities and Y-chromosome microdeletions in infertile Syrian males

Abstract: Infertility is an important health issue affecting numerous couples. Approximately 30-50% of the cases of male infertility is due to unknown reasons. The main genetic factors involved in male infertility are chromosomal abnormalities and Y chromosome microdeletions within the Yq11 region. The genes controlling spermatogenesis located in the Yq11 region are termed azoospermia factor genes (AZF). Klinefelter syndrome (KS) is the most common of the chromosomal anomalies in the infertile male. AZF microdeletions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
5
8
0
1
Order By: Relevance
“…These results supports the previous notion that sex chromosome abnormalities are more frequent in men with azoospermia, while autosomal abnormalities are more frequent in oligozoospermic men [25,32,35,37,40 -42] . KS is the most frequent sex chromosome abnormality among our patients, 127/ 135(94.1%), and this is in accordance with other studies [4,18,23,33,34,43,44] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results supports the previous notion that sex chromosome abnormalities are more frequent in men with azoospermia, while autosomal abnormalities are more frequent in oligozoospermic men [25,32,35,37,40 -42] . KS is the most frequent sex chromosome abnormality among our patients, 127/ 135(94.1%), and this is in accordance with other studies [4,18,23,33,34,43,44] .…”
Section: Discussionsupporting
confidence: 93%
“…In our research, Tthe frequency of numerical chromosomal abnormalities in our study iwas higher than the structural type (11.8% versus 2.4%). Several studies [4,20,28,31,33,38,39] reported similar result [4,20,28,31,33,38,39] . However, in other studies, the frequency of structural abnormalities was higher than numerical ones [18,32] .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Sin embargo, a excepción de los Países Bajos no existe ningún otro país con leyes específicas que permitan utilizar este tipo de evidencia en la casuística actual [28,29].…”
Section: Impacto éTicounclassified
“…Because symptoms are common with other diseases, it is usually underdiagnosed (Abramsky & Chapple, ). Amplification of sequence‐tagged sites (STS) markers using PCR‐based methods is known as a standard technique for detecting AZF microdeletions (Al‐Achkar, Wafa, & Moassass, ; Ambulkar et al., ). The AZF loci are located on the long arm of the Y chromosome (Yq) which contains genes required for normal spermatogenesis (Pryor et al., ).…”
Section: Introductionmentioning
confidence: 99%